Differences in MMP-2 Expression in High- and Low-Grade MPNST and its Correlation with Prognostic Factors - Niniek Hardini; Nurjati Chairani Siregar; Puspita Eka Wuyung (Universitas Muhammadiyah Yogyakarta, 2021)
Malignant peripheral nerve sheath tumor (MPNST) is a soft tissue sarcoma, which is difficult to distinguish from other spindle cell sarcomas. MPNST is hostile, with a high recurrence, and tends to metastasize hematogenously, especially to the lungs. A phase of the metastasis is a degradation of the extracellular matrix, where Matrix Metalloproteinase (MMP) plays an essential role in this process. Gelatinase-type MMP, MMP-2 and MMP-9, can degrade basal membrane and fibrillar collagen to open the invasion pathway. MMP-2 can degrade more collagen and non-collagen extracellular matrix than MMP-9. Therefore, the study aimed to see the relationship between MMP-2 overexpression and histopathological malignancy grading and other clinical prognostic variables. The study was conducted by immunohistochemical staining of MMP-2 in 39 cases, consisting of 19 cases of low-grade MPNST and 20 cases of high-grade MPNST. Subsequently, an analysis of the relationship between MMP-2 overexpression and the malignancy grading and clinical variables was performed, such as age, sex, and tumor size and location. MMP-2 overexpression was seen in 19 (95%) cases of high grade and three (15.8%) cases of low-grade MPNST (p 0.000). The study also found a significant relationship between MMP-2 overexpression and histopathology grading, which may be helpful to define the prognosis.